Enhancement in Performance of Transparent p‐NiO/n‐ZnO Heterojunction Ultrafast Self‐Powered Photodetector via Pyro‐Phototronic Effect. (1st July 2019) - Rana, Amit Kumar; Kumar, Mohit; Ban, Dong‐Kyun; Wong, Ching‐Ping; Yi, Junsin; Kim, Joondong
Abstract: A high‐performance transparent p‐NiO/n‐ZnO heterojunction ultraviolet photodetector with a photovoltaic mode that exploits the pyro‐phototronic effect is demonstrated. The influence of thermal treatment on ZnO films is systematically investigated, and is found to help speed up current flow due to redistribution of the pyroelectric potential within the heterojunction device. The pyrocurrent magnitude is enhanced by 1264.41% for the thermally treated device. In addition, under weak UV illumination (0.43 mW cm −2 ), the thermally treated device exhibits high responsivity and detectivity with respective enhancements over 5460% and 6063% compared to the pristine device. Importantly, an ultrafast response speed with rise time ≈3.92 and decay time ≈8.90 µs is achieved under self‐biased conditions. The device also maintains an impressive transparency of more than 70% in the visible region. Furthermore, the basic pyro‐phototronic properties of the device are thoroughly probed based on the influence of incident light intensity, externally applied bias, and change in transient switching frequencies. This work not only introduces a simple approach but also enables high‐performance self‐powered UV photodetection governed by the pyro‐phototronic effect and demonstrated to be suitable for future transparent optoelectronic devices. Abstract : A self‐driven ultrafast and transparent p‐NiO/n‐ZnO heterojunction ultraviolet (UV) photodetector is realized via the pyro‐phototronic effect. Such a transparent UV photodetector may provide solutions for real‐world applications such as military surveillance, civil monitoring, industry automation control, and space‐based applications. The device can also be applied in smart transparent electronics, particularly in advanced optical devices.